Phylogenetic Analysis of Multi-Drug Resistant Klebsiella pneumoniae Strains From Duodenoscope Biofilm: Microbiological Surveillance and Reprocessing Improvements for Infection Prevention - Ciccozzi, Massimo; Cella, Eleonora; Lai, Alessia; De Florio, Lucia; Antonelli, Francesca; Fogolari, Marta; Di Matteo, Francesco Maria; Pizzicannella, Margherita; Colombo, Benedetta; Dicuonzo, Giordano; Angeletti, Silvia (Frontiers in Public Health, 2019)
Duodenoscopes have been described as potential vehicles of patient-to-patient transmission of multi-drug resistant organisms. Carbapenem-resistant Enterobacteriaceae duodenoscope related infections have been described by the Center for Disease Control and the US Food and Drug Administration consequently to outbreaks occurring in the United States. These evidences suggested that improved microbiological surveillance and endoscope design optimization could represent valid tools to improve infection control. At this aim, in this study an example of duodenoscope microbiological surveillance and reprocessing improvement analyzing strains component of bacterial biofilm by phylogenetic analysis has been proposed. From September 2016 to December 2017, duodenoscope instruments were subjected to microbial surveillance by post-reprocessing cultures of liquid collected by internal channels of instruments after injection and aspiration cycles and membrane filtration. During surveillance seventeen Klebsiella pneumoniae, of which 10/17 (58.8%) MDR and KPC strains, were collected from duodenoscope instruments plus one MDR Klebsiella pneumoniae strain from the rectal swab performed before ERCP procedure in an inpatient. The surveillance allowed evidencing potential failure of reprocessing procedure and performing consequent reprocessing improvements including the contaminated instruments quarantine until their negativity. Phylogenetic analysis of whole genome sequence of duodenoscope strains plus inpatients MDR strains, showed intermixing between duodenoscopes and inpatients, as evidenced by minimum spanning tree and time-scale Maximum Clade Credibility tree. In minimum spanning tree, three groups have been evidenced. Group I including Klebsiella pneumoniae strains, isolated from inpatients before microbiological surveillance adoption; group II including intermixed Klebsiella pneumoniae strains isolated from inpatients and Klebsiella pneumoniae strains isolated from duedonoscopes and group III including Klebsiella pneumoniae strains exclusively from duedonoscope instruments. In the Maximum Credibility Tree, a statistically supported cluster including two Klebsiella pneumoniae strains from duedonoscope instruments and one strains isolated from an inpatient was showed. From the first microbiologic surveillance performed on September 2016 and after the reprocessing improvement adoption, none MDR or susceptible Klebsiella pneumoniae strain was isolated in the following surveillance periods. In conclusion, these results should encourage hospital board to perform microbiological surveillance of duodenoscopes as well as of patients, by rectal swabs culture, and rapid molecular testing for antimicrobial resistance before any endoscopic invasive procedure.